2021
DOI: 10.1111/jocd.14070
|View full text |Cite
|
Sign up to set email alerts
|

Role of vitamin D in treatment of keloid

Abstract: Background Keloid is a benign well‐demarcated overgrowth of fibrotic tissue which extends beyond the original boundaries of a defect. The treatment of keloids is a particular challenge to dermatologists. Intralesional corticosteroid injection has been considered the first‐line treatment for keloids. Vitamin D plays an important role in cell proliferation and differentiation as it slows the progression of tissue fibrosis by keloid fibroblasts and inhibits collagen synthesis in dermal fibrosis. Objectives To eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…Additionally, there may be therapeutic benefit to local administration of vitamin D to keloid tissue. The study by Mamdouh et al suggests that injection of vitamin D into keloids may help reduce their severity, 139 but larger, well‐controlled studies are needed, with longer follow‐up periods, to determine if vitamin D injections have similar efficacy to other injectable drugs, such as triamcinolone and 5‐fluorouracil 10 . Finally, understanding how vitamin D signalling through VDR interacts with other signalling pathways to modulate wound healing may help us to elucidate the molecular mechanisms underlying keloid formation, which could help in design of more targeted and effective therapies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, there may be therapeutic benefit to local administration of vitamin D to keloid tissue. The study by Mamdouh et al suggests that injection of vitamin D into keloids may help reduce their severity, 139 but larger, well‐controlled studies are needed, with longer follow‐up periods, to determine if vitamin D injections have similar efficacy to other injectable drugs, such as triamcinolone and 5‐fluorouracil 10 . Finally, understanding how vitamin D signalling through VDR interacts with other signalling pathways to modulate wound healing may help us to elucidate the molecular mechanisms underlying keloid formation, which could help in design of more targeted and effective therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, calcitriol treatment was able to inhibit TGF‐β1‐induced increases in expression of type I collagen, fibronectin and alpha smooth muscle actin in keloid fibroblasts 136 . Recently, Mamdouh et al performed a clinical trial to investigate the efficacy of vitamin D injection for reduction of keloid severity, which was rated using the Vancouver Scar Scale and ultrasound 139 . Forty patients with keloids 1–5 cm in size were enrolled and keloids were injected with 200,000 IU vitamin D per 1 cm lesion; injections were performed weekly for up to 3–4 sessions.…”
Section: Keloids: More Than Just ‘Scars’mentioning
confidence: 99%
See 1 more Smart Citation
“…This was supported by the study of Mamdouh et al, who observed significant reduction in VSS in a case series of 40 patients with keloids treated with four sessions of weekly intralesional vitamin D injections. 5 In conclusion, vitamin D is a safe, effective and inexpensive treatment modality for keloids. Its lack of AEs such as pigment alteration, atrophy, telangiectasias, etc.…”
mentioning
confidence: 95%
“…Recently, in a study enrolling 40 patients with keloid lesions, weekly intralesional injection of VD with a dose of 0.2 mL (200,000 IU) per 1 cm lesion was beneficial in improving keloid scars [15]. This finding suggests intra­lesional VD as a novel, safe, and effective option for future treatment of keloid lesions.…”
mentioning
confidence: 99%